Atomic Diffusion in Laser Surface Modified AISI H13 Steel - S. N., Aqida; Brabazon, Dermot; Naher, Sumsun (Springer-Verlag, 2013)
This paper presents a laser surface modification process of AISI H13 steel using 0.09 and 0.4 mm of laser spot sizes with an aim to increase surface hardness and investigate elements diffusion in laser modified surface. A Rofin DC-015 diffusion-cooled CO2 slab laser was used to process AISI H13 steel samples. Samples of 10 mm diameter were sectioned to 100 mm length in order to process a predefined circumferential area. The parameters selected for examination were laser peak power, pulse repetition frequency (PRF), and overlap percentage. The hardness properties were tested at 981 mN force. Metallographic study and energy dispersive X-ray spectroscopy (EDXS) were performed to observe presence of elements and their distribution in the sample surface. Maximum hardness achieved in the modified surface was 1017 HV0.1. Change of elements composition in the modified layer region was detected in the laser modified samples. Diffusion possibly occurred for C, Cr, Cu, Ni, and S elements. The potential found for increase in surface hardness represents an important method to sustain tooling life. The EDXS findings signify understanding of processing parameters effect on the modified surface composition.